Jewish Education - Kelman, Ari Y., 1971- (New Brunswick : Rutgers University Press, 2024)
No detailed description available for ""Jewish Education"".
Frontmatter -- Contents -- Foreword -- Introduction The Toughe st K i d i n H ebr e w School -- Part I Terms of the Debate -- Part II State of the Question -- Part III In a New Key -- Conclusion Education Everywhere -- Acknowledgments -- Notes -- Index
Description based upon print version of record.
JSTOR
Keywords: Judaism -- Study and teaching; Jews -- Education; Jewish religious education; Judaïsme -- Étude et enseignement; Juifs -- Éducation.; Éducation religieuse juive; SOCIAL SCIENCE / General